A Study On Human Resource Management Practices In Private Sector Undertakings In Chennai - Kumar, J.Sathish; Suseela, Dr.P. (The journal of contemporary issues in business and government, 2021)
Running a successful business involves more than just making money; it also means being able to manage the people that make it all possible – the employees. Having a well-defined set of Human Resources practices in place makes this an easier task to accomplish. Practices that are legally and ethically sound will produce greater results in business than attempting to manage employees in a haphazard fashion. The best human resources practices create the most effective and efficient method of achieving any objective or task for a business. When aligned with the company mission statement and goals, these practices can address many of the personnel issues that can come up for a business. It is far better for a company to move forward towards meeting goals as one unit, collectively working towards a common goal and having a plan to get there. The most effective human resources practices include capable leadership in the form of a human resources manager or team with experience in employee matters, legal requirements and organizational development. A successful human resources manager will have both the on- the-job experience and education to effectively lead the personnel efforts of a company. In addition, it is important that the company leadership allow an equal place at the table for human resource operatives to best fall in line with company goals.